(untitled) (Journal of the College of Basic Education, 2024)
Islamic law came in an integrated manner and did not legislate anything pertaining to an individual without an individual or a group without a group. It is general and comprehensive, and just as it was concerned with the affairs of men, it is concerned with the affairs of women and legislates its own legislation for them. Women are half of society and are responsible for acts of worship like men, except that they are sometimes excluded for their own reasons, and since Prayer is the mainstay of religion and it is the great pillar of this religion. Islam paid great attention to it, and the Prophet, may God’s prayers and peace be upon him, emphasized prayer in congregation and in mosques. It is a confirmed Sunnah, but this applies to men. Are women like men in this emphasis? The desirability of performing prayer in groups for women is the best because the basis of the rulings for women is always to cover them in order to protect them from any covetous person, and for them to pray in their home is the best according to the agreement of the scholars according to the Sharia texts mentioned, but it is desirable for them to witness the prayers of Muslims in large groups such as the Eid prayer, the rain prayer, etc., so that it can be achieved. For this great virtue, and so that there is a balance in repelling the evils from them and achieving the benefits for them, and this is a great balance with which our noble Islamic Shiites excelled